Optimal Power Systems Restoration Based on Energy Quality and Stability Criteria - Francisco Quinteros; Diego Carrión; Manuel Jaramillo (Energies, 2022)
Electric power systems (EPS) are exposed to disconnections of their elements, such as transmission lines and generation units, due to meteorological factors or electrical failures. Thus, this research proposes a smart methodology for the re-entry of elements that have been disconnected from the EPS due to unforeseen events. This methodology is based on optimal AC power flows (OPF-AC) which allow verifying the state of variables such as voltage, angular deviation, and power (these variables are monitored in normal and fault conditions). The proposed study considers contingencies N-2, N-3, N-4, and N-5, for which the disconnection of transmission lines and generation units are carried out randomly. The analysis of the EPS after the disconnections of the elements is carried out by means of the contingency index, with which the impact that the disconnections of the elements have on the EPS is verified. In this way, the optimal route is generated to restore the elements that went out of operation, verifying that when the elements re-enter the acceptable limits, voltage and voltage angle are not exceeded. According to the results of the methodology used, it was found that NM contingencies can be applied in the proposed model, in addition to considering stability restrictions, modeled as restrictions on acceptable voltage limits, and a new restriction for the voltage angle between the differences of the bars.